Diversifikasi Potensi dan Fungsi Ruang Terbuka Hijau (RTH) Taman Kota di Wilayah Kota Singaraja - Saragih, Abdi Radinal; Astawa, Ida Bagus Made; Sarmita, I Made (Universitas Pendidikan Ganesha, 2021)
This research is located in Singaraja City, Buleleng District, Buleleng Regency with the aim of: (1) Analyzing the potential of City Parks in Singaraja City Area, and (2) Analyzing the diversification of the functions of City Parks in Singaraja City Region. With regard to research conducted in four (4) Public Parks / RTHs in Singaraja City (I Gusti Ngurah Rai Park, Yuwana Asri Park, Soenda Ketjil Park, and Bung Karno Park). Collecting data using new observations, document recording techniques, and literature, which were analyzed using descriptive qualitative methods. The results of this study indicate that: (1) There are 4 Public Parks / RTH in Singaraja City, while Taman I Gusti Ngurah Rai has thematic potentials related to ecological potential, social potential, cultural potential, and economic potential, with the concept of a sports venue, a place for recreation and learning education as well as cultural preservation, through cultural performances. Bung Karno Park, has thematic potentials related to cultural-based ecological potential with the concept of parks as recreation and sports, as well as ecological potentials based on plant needs (offerings) which are closely related to Balinese culture. Yuwana Asri Park, has a thematic potential, focuses as a place to play with educational education and learning for smart children, with the concept of parks as places for recreation and sports, and has economic potential, through trade around the park. Meanwhile, Taman Soenda Ketjil, has a thematic potential, focuses on being a national culinary place which sells culinary and snacks and drinks typical of the Soenda Ketjil (Nusa Tenggara) area with the concept of a park for sports and recreation. Furthermore, the existence of city parks as part of RTH (Green Open Space) has not met the proportion recommended by the government, namely at least 30% consisting of 20% public green open space and 10% consisting of private green open space for urban areas. Therefore, it is hoped that the Buleleng Regency Government, especially the Plantation Office, will organize city parks in accordance with the proportions idealized by the Central Government. (2) Diversification of the functions of the 4 Public City Parks (RTH) in Singaraja City, namely: Singaraja City Park, Bung Karno Park, Yuwana Asri Park, Soenda Ketjil Park or National Park, is in accordance with the devirification of the functions of Public RTH / City Park. both from bio-ecological (physical) functions, productive socio-economic functions and cultural area ecosystems, aesthetic functions.